Communication for development and its new challenges - Armas Castañeda, Segundo (2014)
Most main issues on the Development and Communication for Development Agenda remain the same, but new scenarios, new cooperation partnerships, new issues and new players have arisen thus reshaping the world in this new century and posing new concerns and challenges. In order to face such challenges, promoting building a culture for development to be sustained on the basis of an inclusive democracy with active citizenship guaranteeing governance is important.